ANALISIS PERPUTARAN KAS DALAM MENILAI RETURN ON ASSET PADA PT. PRASIDHA ANEKA NIAGA, Tbk - Netti Natarida Marpaung (PARAMETER, 2019)
The research aim to find out how cash turnover in assessing profitability is measured with return on asset. Object of this research PT. Prasidha Aneka Niaga, Tbk. in 2014-2018 periode. The research is a research of two variables. The independent variable is cash turnover while the dependent variable is profitability. The method used is descriptive qualitative analysis. The analysis technique used is teh technique of cash trunover analysis and profitability analysis that measured with return on asset. Based on the calculation of cash turnover analysis, the results of the cash turnover at PT. Prasidha Aneka Niaga, Tbk for the period of 2014 - 2018 from year to year experiencing fluctuations in cash turnover, but when viewed from industry standards is very good value, because it has a turnover of above ten times each year. For the profitability of PT. Prasidha Aneka Niaga, Tbk also experiences profitability fluctuations every year, if viewed from the industry standards in 2014, 2016 and 2017 is good, while for 2015 and 2018 it is very good. Based on a comparative analysis of cash turnover and profitability over the past five years an average of 20.75 times for cash turnover, while for profitability of 5.62%. It can be interpreted that 20.75 times cash turnover will be followed by 5.62% profitability. And the rest is followed by other factors that did not contribute to this study. From the result of the analysis at PT. Prasidha Aneka Niaga, Tbk over the past five years an average cash trunover of 20,75 times has been found which is very good. Whereas for profitability measured by the retun on assets (ROA) approach, a five years average of 5,63% is good.